2011
DOI: 10.1124/jpet.111.186460
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of COR627 and COR628, Two Novel Positive Allosteric Modulators of the GABAB Receptor

Abstract: The potential efficacy of GABA B receptor agonists in the treatment of pain, drug addiction, epilepsy, cognitive dysfunctions, and anxiety disorders is supported by extensive preclinical and clinical evidence. However, the numerous side effects produced by the GABA B receptor agonist baclofen considerably limit the therapeutic use of this compound. The identification of positive allosteric modulators (PAMs) of the GABA B receptor may constitute a novel approach in the pharmacological manipulation of the GABA B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Several compounds have been shown to have positive GABA B modulatory activity in vitro [e.g., 2,6-di-tert-butyl-4-(3-hydroxy-2,2-dimethylpropyl)phenol (CGP7930) (Urwyler et al, 2001;Adams and Lawrence, 2007), N,N9-dicyclopentyl-2-methylsulfanyl-5-nitro-pyrimidine-4,6-diamine (Urwyler et al, 2003), (R,S)-5,7-di-tert-butyl-3-hydroxy-3-trifluoromethyl-3H-benzofuran -2-one (rac-BHFF) (Malherbe et al, 2008), N-[(1R,2R,4S)-bicyclo [2.2.1]hept-2-yl]-2-m ethyl-5-[4-(trifluoromethyl)phenyl]-4-pyrimidinamine (BHF177) (Guery et al, 2007;Maccioni et al, 2009), methyl-2-(1-adamantanecarboxamido)-4-ethyl-5-methylthiophene-3-carboxylate and methyl-2-(cyclohexanecarboxamido)-4-ethyl-5-methyltiophene-3-carboxylate (Castelli et al, 2011), and 2-{1-[2-(4-chlorophenyl)-5-methylpyrazolo[1,5-a]pyrimidin-7-yl]-2-piperidinyl}ethanol (Perdona et al, 2011)]. Their positive GABA B modulatory activity in vitro was evidenced by enhancing GABA, and, for all compounds except BHF177, also by enhancing the GABA B receptor agonist baclofen.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds have been shown to have positive GABA B modulatory activity in vitro [e.g., 2,6-di-tert-butyl-4-(3-hydroxy-2,2-dimethylpropyl)phenol (CGP7930) (Urwyler et al, 2001;Adams and Lawrence, 2007), N,N9-dicyclopentyl-2-methylsulfanyl-5-nitro-pyrimidine-4,6-diamine (Urwyler et al, 2003), (R,S)-5,7-di-tert-butyl-3-hydroxy-3-trifluoromethyl-3H-benzofuran -2-one (rac-BHFF) (Malherbe et al, 2008), N-[(1R,2R,4S)-bicyclo [2.2.1]hept-2-yl]-2-m ethyl-5-[4-(trifluoromethyl)phenyl]-4-pyrimidinamine (BHF177) (Guery et al, 2007;Maccioni et al, 2009), methyl-2-(1-adamantanecarboxamido)-4-ethyl-5-methylthiophene-3-carboxylate and methyl-2-(cyclohexanecarboxamido)-4-ethyl-5-methyltiophene-3-carboxylate (Castelli et al, 2011), and 2-{1-[2-(4-chlorophenyl)-5-methylpyrazolo[1,5-a]pyrimidin-7-yl]-2-piperidinyl}ethanol (Perdona et al, 2011)]. Their positive GABA B modulatory activity in vitro was evidenced by enhancing GABA, and, for all compounds except BHF177, also by enhancing the GABA B receptor agonist baclofen.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds have been shown to have positive GABA B modulatory activity in vitro [2,6-di-tert-butyl-4-(3-hydroxy-2,2-dimethylpropyl)phenol (CGP7930) (Urwyler et al, 2001;Adams and Lawrence, 2007), N, (Urwyler et al, 2003), (R,S)-5,7-di-tert-butyl-3-hydroxy-3-trifluoromethyl-3H-benzofuran-2-one (rac-BHFF) (Malherbe et al, 2008), N- [(1R,2R,4S)bicyclo[2.2.1]hept-2-yl]-2-methyl-5-[4-(trifluoromethyl)phenyl]-4-pyrimidinamine (BHF177) (Guery et al, 2007;Maccioni et al, 2009), methyl-2-(1-adamantanecarboxamido)-4-ethyl-5-methylthiophene-3-carboxylate (COR627), and methyl-2-(cyclohexanecarboxamido)-4-ethyl-5-methylthiophene-3-carboxylate (COR628) (Castelli et al, 2012)], evidenced by enhancing GABA, and, for all compounds except BHF177, also by enhancing the GABA B receptor agonist baclofen. In vivo results suggest positive GABA B receptor modulators to have anxiolyticand antidepressant-like properties in elevated-maze and forced-swimming tests, respectively (Cryan et al, 2004;Frankowska et al, 2007;Jacobson and Cryan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Castelli et al (75) reported two novel PAMs (COR627 and COR628) in 2011. They selected six metabotropic γ-aminobutyric acid B (GABA B ) receptor PAMs with diverse structures from literatures (76)(77)(78)(79), and generated a fivefeatures pharmacophore model, including three hydrophobic sites (H1-H3), one aromatic group (R), and one hydrogenbond donor (D).…”
Section: Pharmacophore-based Virtual Screeningmentioning
confidence: 99%